2017
DOI: 10.1186/s12889-017-4840-4
|View full text |Cite
|
Sign up to set email alerts
|

High variability of TB, HIV, hepatitis C treatment and opioid substitution therapy among prisoners in Germany

Abstract: BackgroundIn Germany, medical care of prisoners is completely separated from extramural health care. The extent and quality of medical care among prisoners in Germany are therefore largely unknown. We performed a secondary data analysis of pharmacy sales data for tuberculosis (TB), HIV, hepatitis C (HCV) and opioid substitution treatment (OST) delivered to prisons in 11 federal states (FS) in Germany between 01/2012 and 03/2013. The aims of this study were to assess (i) the treatment availability for the selec… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
1
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 35 publications
0
8
1
3
Order By: Relevance
“…This discrepancy may reflect the differences in the OAT practices at the transition from the extramural to the intramural sector across various federal states. For instance, in Saarland, no prisons are supplied with OAT medicines, and in Lower Saxony, all prisons are supplied with such substances (24). Our research demonstrated lower rates of opioid dependence among women than previous studies, which estimated dependence on opioids between 27-50% in the women's custodial setting (55,56).…”
Section: Access To Oat During Detentioncontrasting
confidence: 43%
See 4 more Smart Citations
“…This discrepancy may reflect the differences in the OAT practices at the transition from the extramural to the intramural sector across various federal states. For instance, in Saarland, no prisons are supplied with OAT medicines, and in Lower Saxony, all prisons are supplied with such substances (24). Our research demonstrated lower rates of opioid dependence among women than previous studies, which estimated dependence on opioids between 27-50% in the women's custodial setting (55,56).…”
Section: Access To Oat During Detentioncontrasting
confidence: 43%
“…Thus, compensation imprisonment represented a predictor for OAT most likely due to factors related to this sub-prison. Several authors discuss differences in attitudes held toward liberal and harm-reduction drug politics-which translate into different institutional policies and regulations-as a main reason for the general hesitation to use OAT in prisons and its high implementation variability between different federal states (24,30,34,60). Yet the variability of implementation seems not only to be limited to the national level (24), but also to apply to the federal state level.…”
Section: Access To Oat During Detentionmentioning
confidence: 99%
See 3 more Smart Citations